Aneugenic effect of sodium arsenite on human lymphocytes in vitro: an individual susceptibility effect detected - Vega, Libia; Gonsebatt, María E.; Ostrosky-Wegman, Patricia (Mutation Research, 1995)
Arsenic is a well known carcinogenic environmental pollutant although its mechanism of action remains unknown. Since alterations in chromosome segregation have been observed in individuals exposed to high concentrations of arsenic in the drinking water, the aneuploidogenic potential of arsenic was evaluated in vitro. Whole blood cultures were incubated for 72 h and treated with various concentrations of sodium arsenite for the last 24 h. Cells were harvested and samples were processed specially for aneuploidy evaluation. The number of chromosomes in 200 metaphases of first and second division cells was scored. A dose-related effect was observed: the highest concentration (10 −2 μM) induces 28.33% and 22.4% hyperploid cells in first and second division respectively and 29% tetraploid cells. The colchicine-like effect of arsenic was also evaluated. Mitotic arrest was evaluated in cultures treated for the last 2 h. Sodium arsenite can produce 40.24% and 12.93% of the colcemid effect (mitotic arrestant effect at 10 −2 μM and 10 −10 μM respectively). A different individual susceptibility effect was observed in both parameters and confirmed with the chromosome aberrations levels induced by arsenic in the same donors. Data indicate that sodium arsenite has an aneuploidogenic and a mitotic arrestant effect.